Digital Healthcare and the Integration of Telemedicine and Virtual Care in General Practices of Healthcare Workforce Dynamics - Abosarha, Aziza Ibrahim Saeed; Aloufi, Saif Hassan Rafid; Alqasimi, Mohmmed Abdullah; Alharbi, Emad Jahaz Salem; Alsomali, Laila Abdullah Omar; Alqurashi, Ghazi Nahi khalifuh; Mashi, Mofarh Mohammed Yahya; Alqarni, Mohammed Abdullah; Saeed, Hashim Abdullah Abdulhadi; Althaqafi, Abdullah yousef Abdullah (Journal of Ecohumanism, 2024)
The use of digital technologies, and more specifically telemedicine and virtual care, has redefined general practices and healthcare services as well as the workforce. This paper focuses on how this integration has occurred and impacted the care provider, workplace systems, and, most importantly, the patients. This paper examines the literature and analyzes data to identify problems, prospects, and consequences of telemedicine and virtual care. Moreover, the study uncovers the effects of telemedical advancement on the healthcare workforce's education, productivity, utilization, and values. Finally, recommendations are made for enhancing the use of new elements of digital healthcare tools.